A link between high serum levels of human chorionic gonadotrophin and chorionic expression of its mature functional receptor (LHCGR) in Down's syndrome pregnancies - Spencer Kevin; Loosfelt Hugues; Papageorghiou Aris; Chambers Anne E; Smallwood Alan; Banerjee Subhasis; Campbell Stuart; Nicolaides Kypros (BMC, 2005)
Abstract Human chorionic gonadotrophin (hCG) is released from placental trophoblasts and is involved in establishing pregnancy by maintaining progesterone secretion from the corpus luteum. Serum hCG is detected in the maternal circulation within the first 2-3 wks of gestation and peaks at the end of the first trimester before declining. In Down's syndrome (DS) pregnancies, serum hCG remains significantly high compared to gestation age-matched uncompromised pregnancies. It has been proposed that increased serum hCG levels could be due to transcriptional hyper-activation of the CGB (hCG beta) gene, or an increased half life of glycosylated hCG hormone, or both. Another possibility is that serum hCG levels remain high due to reduced availability of the hormone's cognate receptor, LHCGR, leading to lack of hormone utilization. We have tested this hypothesis by quantifying the expression of the hCG beta (CGB) RNA, LHCGR RNA and LHCGR proteins in chorionic villous samples. We demonstrate that chorionic expression of hCG beta (CGB) mRNA directly correlates with high serum hCG levels. The steady-state synthesis of LHCGR mRNA (exons 1-5) in DS pregnancies was significantly higher than that of controls, but the expression of full-length LHCGR mRNA (exons 1-11) in DS was comparable to that of uncompromised pregnancies. However, the synthesis of high molecular weight mature LHCGR proteins was significantly reduced in DS compared to uncompromised pregnancies, suggesting a lack of utilization of circulating hCG in DS pregnancies.